Concentration threshold for polyethylene microplastics impacting nitrogen transfor-mation in heterotrophic nitrification-aerobic denitrification systems - Xue Bai; Mengying Yi; Lang Ran; Weidong Xiao; Ran Sun; Zherui Zhang; Sihai Hu; Yaoguo Wu (Bioresource Technology, 2027)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Groundwater dynamics induced by tunneling and reservoir filling at the site of Kala hydropower project - Ao Liu; Ying-Feng Zhang; Yi-Feng Chen; Ran Hu; Zhibing Yang; Jia-Qing Zhou; Hai-Sheng Zheng; Heng-Yi Gan; Bin Chen; En-Ming Zhang (Tunnelling and Underground Space Technology, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Decoupling of abundance and activity: Low-abundance comammox contributes substantially to ammonia oxidation in N-fertilized paddy soils - Yi-Xuan Zhang; Wen-Jing Qin; Ran Jiang; Peng Li; Man-Young Jung; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

Effects of wastewater flow direction on sulfur-based autotrophic denitrification processes: operational patterns, denitrification performance and response mechanisms - Daheng Ren; Heng Dong; Wenke He; Zhiqiang Zuo; Xiangli Zeng; Xuchen Ba; Yang Yu; Haoran Xu; Guijiao Zhang; Ran Zeng; Jiamin Xu; Na Zhang; et al. (Chemical Engineering Journal, 2026)

Synergistic effects of co-pyrolyzed rice straw/non-woven fabric biochar on soil enhancement and rice growth promotion - Shuo Su; Jiachen Zhu; Tian Xie; Zhihua Zhang; Yi Zhu; Yu Xie; Yuting Ran; Lingling Yao; Jie Qin; Jing Huang; Junxin Zhou; Zhi Zhou; et al. (Paddy and Water Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A degradable, highly tough, and resilient nanocomposite hydrogel for self-powered wearable sensors and a deep learning-assisted recognition system - Xiang Di; Weiqiang Ran; Yi Wang; Ruotong Zhang; Bo Yu; Baohui Li; Jiawen Hou; Chungang Yuan (Chemical Engineering Journal, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Effect of overlying low-permeable soil on underwater shield tunnel response to water level fluctuation - Dong-Mei Zhang; Hao-Ran Lai; Yi-Yao Shen; Feng Du (Tunnelling and Underground Space Technology, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Decoding the dynamic formation of bolus: A multimodal fusion and simulation framework for texture perception-regulated oral processing - Che Shen; Xinyu Jiang; Lizhang Wu; Zidong Chen; Zihao Li; Ran Wang; Wenxi Qi; Yi Zhang; Xinying Zhou; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Regulating radical pathways in highly selective photon–phonon synergistic methane oxidation by tuning Au nanoparticle size over Au–ZrO2 - Shengrong Zhou; Zitong Bao; Yuhang Shao; Xiaolei Guo; Xinru Jiang; Yi Xie; Dong Fang; Ran Ran; Guangzhao Li; Feng Zeng; Hongwei Zhang (Chemical Engineering Journal, 2026)

Hydraulic performance of circular tunnels with interior drainage boundaries subjected to water level fluctuation - Hao-Ran Lai; Dong-Mei Zhang; Yi-Yao Shen; Bin-Lin Gan (Transportation Geotechnics, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Completing the puzzle of aged microplastics towards microalgae at environmental concentration: effects of polymer type, size, aging method, and aging duration - Ming-Zhi Shen; Liu Yang; Yi-Ran Zhai; Jing-Han Wang; Zhan-You Chi; Qiang Zhang (Journal of Cleaner Production, 2026)

Unveiling the regulation of biochar and ferrihydrite on organic carbon stabilization, CH4 emission and microbial community in paddy soil - Ran Zhang; Yujing Gu; Linrui Zhong; Yuantao Xu; Fanzhi Qin; Hong Qin; Qian Liu; Jiali Cheng; Jiahui Lei; Jingwen Yan; Yi Yin; Yue Lu (Journal of Environmental Sciences, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Structure-driven RNA remodeling underlies broad substrate recognition by NSUN2 - Qian Hu; Wen Yang; Yunyun Yu; Ran Yi; Yutong Zhang; Leyuan Duan; Fudong Li; Kaiming Zhang; Qingguo Gong; Shanshan Li (Science China Life Sciences, 2026)

Deep learning-based downscaling of ocean surface vector wind over the Taiwan Strait and its adjacent seas with Pangu-weather - Jun Yi; Xiang Li; Jiuke Wang; Yunfei Zhang; Ran Yang; Yafei Nie (Journal of Marine Systems, 2026)

Compartment-specific assembly and functional characterization of the bacterial microbiome in a Pinus radiata- Lactarius deliciosus plantation system - Jing Yuan; Yanliang Wang; Xueqiong Zhang; Zhuyue Yan; Ran Wang; Chengmo Yang; Xinhua He; Jesús Pérez-Moreno; Fuqiang Yu; Yi Zheng (Applied Soil Ecology, 2026)

Transforming erosion-prone basin into carbon sink: the role of check dams in regulating carbon cycle in a semi-arid basin - Yi Zeng; Nufang Fang; Lishan Ran; Ying Yu; Zhengang Wang; Fengbao Zhang; Zhihua Shi (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

Revegetation mechanisms and influence factor in alpine mining areas: a case study of the Muli mining area, Qinghai-Tibet Plateau - Kaixin Zhang; Qingqiu Hou; Haibo Feng; Linxue Ju; Jianwei Zhou; Jun Li; Ruimin Xiong; Yi Zhu; Xiaoming Zheng; Ran Li; Chunguang Wang (Plant and Soil, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Analysis of the resistance and flow characteristics of a square diffuser under adjacent influence conditions based on design of experiments - Haimeng Li; Wei Xu; Ran Gao; Xinyu Zhang; Chi Zhang; Yan Tian; Yi Wang; Ruoyin Jing (Building and Environment, 2026)

Does corporate climate risk promote climate response actions? Empirical evidence from China - Ran Yi; Yunfan Zhang; An Chen (Mitigation and Adaptation Strategies for Global Change, 2026)

Decoding aroma perception of grilled lamb skewers: an EEG-MambaFusionNet framework integrating TDS and GC-IMS - Che Shen; Wenxi Qi; Yi Zhang; Ran Wang; Qi Jin; Kezhou Cai; Bo Wang; Dengyong Liu (Food Chemistry, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Alkali promotion in nonmetallic boron-based catalysts: Establishing structure–activity correlations for selective methane oxidation - Ran Yan; Penghui Li; Siyu Liu; Xindi Zhang; Leisu Li; Chenxin Zhang; Shaolong Wan; Jingdong Lin; Xiaodong Yi; Lingtao Liu; Shuai Wang (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Peijinzhouia sedimentorum gen. Nov., sp. nov., isolated from polymetallic nodule fields of the Eastern Pacific, and proposal of the family Peijinzhouiaceae fam. Nov. - Yi-Ran Zhang; Xu-Ya Lv; Zhen Rong; Xue-Wei Xu; Yue-Hong Wu (Systematic and Applied Microbiology, 2026)

Responses of carbon monoxide photoproduction in surface seawater to environmental changes under simulated solar radiation - Xuan Ji; Ming-Liang Zhao; Yi-Ran Jia; Cai-Jie Zhang; Qi-Mei Du; Jing Zhang; Gui-Peng Yang (Marine Chemistry, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Promoting nitrogen removal in low C/N wastewater treatment by S0 packed-bed process: Post polishing or via disproportionating sulfidogenesis enhancement - Cong Fang; Guijiao Zhang; Wenwei Liao; Ran Zeng; Na Zhang; Bin Gao; Jiamin Xu; Chengyan Liu; Aijie Wang; Hao-Yi Cheng (Chemical Engineering Journal, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

A self-activated CO-releasing microneedle patch for treating diabetic foot ulcer biofilm infection - Linpei Li; Menghao Wei; Haixia Zhang; Zilong Zhang; Xiaojuan Zhao; Zhichao Ran; Yi Li; Yanwei Yang; Ningning Song; Chaoqun Liu (Chemical Engineering Journal, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Machine Learning Improves Mesoscale Offshore Wind Resource Assessment over the Yellow Sea - Haixing Gong; Kan Yi; Dinghua Yang; Wenyu Huang; Chenqing Fan; Ran Hao; Lina Sha; Mengke Deng; Hao Zhang (Journal of Meteorological Research, 2025)

A highly fractionated origin for the Yanshanian water-rich A-type granite in the Southern Great Xing’an Range, NE China: Insights from zircon and monazite geochemistry - Zi-Yi Wang; Hao Yang; Hao-Ran Wu; Zhi-Chao Zhang; Zheng Ji; Yu Dong; Wen-Chun Ge (Journal of Asian Earth Sciences, 2025)

Post-heat treatment and pectin addition affect protein digestion and absorption release kinetics in pigs through microstructural and rheological modifications - Xiyu Qin; Xiuying Wu; Caiziyu Yu; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Huifang Cai; Mengxuan Lai; Lili Qiu; Yanling Hao; Ran Wang; Yixuan Li; et al. (Food Chemistry, 2025)

Heat treatment affects gastric digestion kinetics but not amino acid bioavailability of milk proteins: a pig study - Xiyu Qin; Caiziyu Yu; Xiaolu Geng; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Menghui Wang; Xiaomin Ren; Yanling Hao; Ran Wang; Yixuan Li; Pengjie Wang; et al. (Food Chemistry, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Ceritinib (LDK378) inhibits laryngeal squamous cell carcinoma progression via regulating ROS-induced mitochondrial apoptosis and inducing oxidative stress - Yue Wang; Xiaoli Ren; Pengyan Liu; Ran An; Wenjing Li; Licheng Xu; Yaoyao Dong; Xiaolin Xu; Yi wang; Lei Zhang; Linli Tian (Toxicology and Applied Pharmacology, 2025)

Impact of tris (2-chloropropyl) phosphate and triphenyl phosphate on honeybee (Apis mellifera L.) midgut health: Assessing toxicity and potential mitigation with melatonin - Rongyi Ye; Yihan Wang; Kebo Wang; Ran Yi; Fengjiao Sun; Nan Huang; Tianliang Zhang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Multifunctional bending sensor based on PLA hierarchical porosity: smart wearable device with wide range response, self-powered capability and biodegradable - Jun Hou; Danqing Zhang; Qi Ran; Geran Yin; Manlin Wang; Wenhao Yang; Hua Wang; Yi Xiong; Xin Liu; Heng Pan; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Causal Relationship Between Serum Zinc Levels and Diabetic Kidney Disease (DKD): A Plasma Proteomics Mediation Study - Chunbo Zhao; Tingting Pan; Wei Liu; Fanqian Cheng; Xiaoxuan Zhao; Shuxin Yu; Yi Yang; Ran Zhang; Weixia Sun (Biological Trace Element Research, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Feedback inhibition derived from hydrogen sulfide in microbial sulfidogenic process via elemental sulfur disproportionation - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xuchen Ba; Wenyan Mao; Wenke He; Cong Fang; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Efficient mining of natural products from Mangrove streptomyces using NP-PRESS - Lin Yu; Junxiao Wang; Kai Jin; Fan Xu; Yi Huang; Ran Zhang; Yihan Wu; Fei Xu (Archives of Microbiology, 2025)

Soil health assessment of urban forests in Nanchang, China: Establishing a minimum data set model - Fei Huang; Jiamei Tu; Foyi Zhang; Jingwang Ran; Yi Wang; Wei Liu; Wenxuan Chen; Xinyao Wang; Qiong Wang (Soil Biology and Biochemistry, 2025)

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

The interaction between banana polyphenols and starch improves the bioavailability of polyphenols after non-co-heating complexation - Yajuan Qin; Jingfeng Ran; Xiaoai Chen; Xuan Zhang; Yutong Zhang; Fei Xu; Kexue Zhu; Cuiping Yi; Yanjun Zhang (Food Hydrocolloids, 2025)

The simulated in vitro infant gastrointestinal digestion of lipid droplets covered with milk fat globule membrane components: The role of interface layers - Zhixi Li; Yu Cao; Xiankang Fan; Hui Zhou; Pengjie Wang; Hao Zhang; Yi Wang; Ran Wang; Jie Luo (Food Research International, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Nitrate ameliorates myelin loss and cognitive impairment in Alzheimer’s disease through upregulation of neuronal sialin and subsequent inhibition of TPPP phosphorylation - Xinyue Chen; Geng Hu; Lirong Chang; Xiaoyu Li; Yi Tang; Yan Wu; Ran Zhang; Chunmei Zhang; Jinsong Wang; Xue Wang; Songlin Wang (Science Bulletin, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Simultaneous extraction of flavonoids and saponins from functional food via basic deep eutectic solvent-assisted mechanochemical extraction - Yi-Wen Wu; Jie Zhang; Xin-Ran Ma; Jun Cao (Food Chemistry, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Bed-immersion-ratio variation as an efficient strategy to regulate denitrification efficiency directionally in elemental sulfur packed-bed reactors - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xinjie Chen; Wenyan Mao; Xiangli Zeng; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Study on the Spatial and Temporal Evolution Law of Large-Size Fracture Propagation in Deep Coalbed Based on Acoustic Emission Technology - Zhihong Zhao; Tianyu Wu; Jianchun Guo; Jiale He; Xiaoyong Wen; Yi Liu; Ran Zhang (Rock Mechanics and Rock Engineering, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

On the permeability-surface area-porosity relationship for dissolving porous media - Kai Li; Ran Hu; Ya-Nan Zhang; Zhibing Yang; Yi-Feng Chen (Advances in Water Resources, 2025)

Assessment of wetland ecological restoration effect based on fuzzy analytic hierarchy process: a case study of Tianjin Qilihai Wetland - Ran Zhou; Yi Zhang; Shitao Peng; Yisheng Wang; Mingxin Dai; Ningning Hong; Hui Tong; Baocui Liang; Shaopeng Lu; Wu Hong (Environmental Monitoring and Assessment, 2025)

CSF multi-omics of intracerebral hemorrhage from onset to reperfusion underscores lipid metabolism in functional outcome - Yibin Jiang; Sin Man Lam; Shuixian Zhang; Huan Miao; Yong Zhou; Qian Zhang; Tengyuan Zhou; Hui Feng; Ning Ding; Haomiao Wang; Ran Luo; Yi Yin; et al. (Science Bulletin, 2025)

Suspended sediment (SPS) triggers nitrogen retention by altering microbial network stability and electron transport behavior during the aerobic-anoxic transition - Xiaoyan Liu; Tingting Pei; Guojia Xu; Tinglin Huang; Yaoguo Wu; Xiaowei Jin; Yi Cao; Ran Sun; Sihai Hu; Pathmalal M. Manage; Xiang Liu; Tao Liu; et al. (Journal of Environmental Management, 2025)

Full-spectral response of mesoporous Z-scheme nanoheterojunction NaYF4:Yb,Tm@ZnO/BiOI photocatalysts for simultaneous contaminant and pathogen elimination in wastewater - Wenqi Liu; Changyuan Zhang; Ran Yi; Mengyu Di; Dan Shan; Yang Wu; Xiaoyu Linghu; Chang Li; Baiqi Wang (Process Safety and Environmental Protection, 2024)

Harnessing natural light: Novel nanoheterojunction photocatalyst NaGdF4:Yb,Tm@TiO2/Cu2(OH)2CO3 for actual wastewater remediation - Mengyu Di; Wenqi Liu; Dan Shan; Yue Zhao; Changyuan Zhang; Yankun Wang; Ran Yi; Yang Wu; Jing Zheng; Baiqi Wang (Journal of Environmental Management, 2024)

Combined effect of flocculation and ammonia stripping on different biogas slurries - Haorui Zhang; Shunli Zhang; Yanyan Zhang; Ahmed Alengebawy; Yi Ran; Shisheng Song; Ping Ai (Journal of Environmental Chemical Engineering, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Vitamin consumption and the ontogenesis of cathepsins and antioxidant capacity in developing embryos of turbot, Scophthalmus maximus - Xuehong Tong; Sudan Ran; Yiqiu Feng; Linxi Cao; Yi Wang; Yueqin Wang; Yutian Zhuang; Xuexue Zhang (Aquaculture International, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Nonlinear effects of agricultural drought on vegetation productivity in the Yellow River Basin, China - Yujie Ding; Lifeng Zhang; Yi He; Shengpeng Cao; Andrei Gusev; Yan Guo; Ling Ran; Xiao Wei; Filonchyk Mikalai (Science of The Total Environment, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Green synthesis of biomass-derived porous carbon for electrochemical detection of heavy metal ions: Methods, properties, and applications - Bo Zhang; Gangxin Ren; Linghao Ran; Mengzhao Liu; Ping Geng; Weiming Yi (Journal of Environmental Chemical Engineering, 2024)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Robust fatigue markers obtained from muscle synergy analysis - Chen Zhang; Zi-jian Zhou; Lu-yi Wang; Ling-hua Ran; Hui-min Hu; Xin Zhang; Hong-qi Xu; Ji-peng Shi (Experimental Brain Research, 2024)

Effect of vegetation on unsaturated soil hydraulic and the slope stability under rainfall - Ji-Peng Wang; Mo-Han Bai; Yi-Ran Tan; Shangqi Ge; Xu-Guang Gao; Abdelali Dadda; Jing-Yi Shen; Jiong Zhang (Rhizosphere, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Taming the anchor and conversion of polyselenides with a self-reinforcing host in lithium–selenium batteries - Hongyan Li; Wenda Dong; Yueqiang Cao; Tarek Barakat; Marvin Laboureur; Mao-Jin Ran; Zhi-Yi Hu; Hongxian Zhang; Cheng-Bin Jin; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Sludge biolysis pretreatment to reduce antibiotic resistance genes (ARGs): Insight into the relationship between potential ARGs hosts and BALOs' preferred prey - Siyuan Zhang; Tingting Cui; Xiaowen Liu; Manjun Zhan; Xin Song; Yi Xu; Ran Yu (Water Research, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Effect of recycled polypropylene on migration of six processing aids in polypropylene film to milk - Yi-Qi Liu; Ze-Kun Li; Hao-Ran Zhang; Zhi-Wei Wang; Chang-Ying Hu (Food Packaging and Shelf Life, 2024)

Tissue-specific responses and interactive characteristics of crop-microbe "One Health" system to soil chromium and ofloxacin pollution - Jia-Min Xu; Yaru Zhang; Kai Wang; Guodong Zhang; Ying Liu; Hao-Ran Xu; Hu-Yi Zi; Ai-Jie Wang; Yao Lv; Kun Xu; Hao-Yi Cheng (Process Safety and Environmental Protection, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Improved efficiency and stability using a novel elemental sulfur-based moving-bed denitrification process - Jia-Min Xu; Hu-Yi Zi; Hao-Ran Xu; Yi-Fan Zhang; Da-Heng Ren; Ran Zeng; Gui-Jiao Zhang; Aijie Wang; Hao-Yi Cheng (Water Research, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Promoting nitrogen conversion in aerobic biotransformation of swine slurry with the co-application of manganese sulfate and biochar - Xuan Wu; Xinyu Zhao; Guorong Yi; Wanqiang Zhang; Runyu Gao; Daniel Kuok Ho Tang; Ran Xiao; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Journal of Environmental Management, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Synthesis, antifungal activity and mechanism of action of novel chalcone derivatives containing 1,2,4-triazolo-[3,4-b]-1,3,4-thiadiazole - Wenliang Zhan; Ran Zhou; Piao Mao; Chunmei Yuan; Tao Zhang; Yi Liu; Jiao Tian; Hua Wang; Wei Xue (Molecular Diversity, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Spatiotemporal evolution of agricultural drought and its attribution under different climate zones and vegetation types in the Yellow River Basin of China - Yujie Ding; Lifeng Zhang; Yi He; Shengpeng Cao; Xiao Wei; Yan Guo; Ling Ran; Mikalai Filonchyk (Science of The Total Environment, 2024)

Different binding properties of odorant-binding protein 8 to insecticides in Orius sauteri - Zhe-Ran Wu; Yi-Wen Pei; Xiao-Qing Zhang; Min Lu; Xiao-Long Liu (Pesticide Biochemistry and Physiology, 2024)

LSTM time series NDVI prediction method incorporating climate elements: A case study of Yellow River Basin, China - Yan Guo; Lifeng Zhang; Yi He; Shengpeng Cao; Hongzhe Li; Ling Ran; Yujie Ding; Mikalai Filonchyk (Journal of Hydrology, 2024)

Experimental and computational insight into the role of cobalt and phosphorus in boosting Volmer and Heyrovsky steps of Ni in alkaline hydrogen evolution reaction - Wei Xu; Xian-Qing Tang; Zhen Zhang; Yi-Ran Wang; Jian-Long Luo; Isack Bulugu; Wen-Jie Yin; Xin Tang; Yu Shen (Fuel, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Modification engineering of TiO2-based nanoheterojunction photocatalysts - Yue Zhao; Yue Shu; Xiaoyu Linghu; Wenqi Liu; Mengyu Di; Changyuan Zhang; Dan Shan; Ran Yi; Baiqi Wang (Chemosphere, 2024)

Contrasting lake changes in Tibet revealed by recent multi-modal satellite observations - Jiangjun Ran; Lin Liu; Guoqing Zhang; C.K. Shum; Jiahui Qiu; Ruigang Hu; Jianping Li; Junhuan Peng; Cheinway Hwang; Yi Luan; Yue Sun; Min Xu; et al. (Science of The Total Environment, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Changes in Accessibility of Chinese Coastal Ports to Arctic Ports under Melting Ice - Ran Zhang; Yi Zuo; Zhuo Sun; Shuang Cong (Journal of Marine Science and Engineering, 2023)
Global warming has accelerated the melting of Arctic sea ice, providing favorable conditions for Arctic shipping. Arctic ports are gaining prominence in shipping networks and international trade. Accessibility is a key indicator of port facilitation, and identifying trends in Arctic port accessibility holds significance for Arctic route planning and port development. To achieve this, this paper develops a modeling framework for assessing the accessibility of Arctic ports. First, we utilize the Coupled Model Intercomparison Project (CMIP6) model to predict sea ice conditions and quantify the navigation risk for open water (OW) vessels and Arc4 ice-class (Arc4) vessels during the summer months of 2030–2050. The A-star (A*) algorithm is then used to plan the vessel’s shortest route while avoiding high-risk waters. Finally, changes in the accessibility of Arctic ports are calculated by using an improved gravity model. The framework is applied for the quantitative analysis of the accessibility of Chinese coastal ports to Arctic ports. The results indicate that accessibility to Arctic ports will gradually increase for all Chinese ports in the future, with the port of Shanghai continuing to maintain its prominence under the trend of melting sea ice.

Analysis of Stress–Strain Characteristics and Signal Coherence of Low-Specific-Speed Impeller Based on Fluid–Structure Interaction - Fengquan Qiao; Yi Sun; Di Zhu; Mingkun Fang; Fangfang Zhang; Ran Tao; Ruofu Xiao (Journal of Marine Science and Engineering, 2023)
In this study, an analysis of a low-specific-speed pump is carried out based on the methods of one-way and two-way fluid–structure interactions (FSIs). This study analyzes the influence of FSIs on the internal flow field and external characteristics of the pump. Utilizing a two-way FSI, the signal coherence analysis method is employed to analyze the coherence of signals between the flow field and the structural field. Addressing the issue of a lack of a connection between the two signals, this study bridges a gap in the existing research. The results indicate that different interaction methods have certain influences on impeller stress and deformation. However, in both coupling modes, the maximum deformation and the maximum equivalent stress have the same distribution position. The head error obtained using the two-way coupling method is lower than that of the uncoupled results, which indicates that the two-way FSI calculation results are closer to the experimental results. The pressure pulsation signals at the interface of the impeller and volute exhibit strong coherence with the structural field signals. For low-specific-speed centrifugal pumps, establishing a clear connection between the flow field signals and structural field signals will help guide further optimization of their performance through design.

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

An electroconductive hydrogel with injectable and self-healing properties accelerates peripheral nerve regeneration and motor functional recovery - Zhenwei Yi; Fangke Zhan; Yijia Chen; Ran Zhang; Haodong Lin; Liming Zhao (Chemical Engineering Journal, 2023)

A long way to go: impacts of urbanization on migrants’ livelihoods and rural ecology in less industrialized regions - Zhi-qi Zhang; Ming-jing Li; Wen-jun Li; Yi-ran Wei; Yi-lu Shi (Journal of Mountain Science, 2023)

Degradation of Levofloxacin by a green zero-valent iron-loaded carbon composite activating peroxydisulfate system: Reactivity, products and mechanism - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Wen-Xuan Zhang; Jing-Yi Liang; Xie Chen; Jing-Wei Xu; Zeng-Hui Diao (Chemosphere, 2023)

Sulfur-aided aerobic biostabilization of swine manure and sawdust mixture: Humification and carbon loss - Yang Wang; Jingwen Wang; Guorong Yi; Xuan Wu; Xiu Zhang; Xu Yang; Kuok Ho Daniel Tang; Ran Xiao; Zengqiang Zhang; Guangzhou Qu; Ronghua Li (Bioresource Technology, 2023)

A versatile organic silicate aluminum hybrid coagulant for broad-spectrum removal of heavy metal ions - Jin-Wei Liu; Tao Fu; Guang-Dong Sun; Xiao-Ran Shen; Sheng Liu; Yang He; Yi Xu; Hua-Zhang Zhao (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Fluoride resistance capacity in mammalian cells involves global gene expression changes associate with ferroptosis - Yi Zhang; Yimin Fang; Shen Zhao; Jialong Wu; Chenkang Lu; Lai Jiang; Shujun Ran; Jia Wang; Fei Sun; Bin Liu (Chemico-Biological Interactions, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Interspecific rootstocks improve the low-temperature resistance of bitter gourd through sucrose and nitrogen metabolism regulation - Le Liang; Huashan Lian; Huanxiu Li; Yiping Dong; Wanjia Tang; Ran Zhang; Xuemei Peng; Xiaomei Li; Yi Tang (Acta Physiologiae Plantarum, 2023)

Microbial electrochemical technologies assisted nitrogen recovery from different wastewater sources: Performance, life cycle assessment, and challenges - Siyuan Zhai; Dexin Zhang; Wenzong Liu; Bo Wang; Bin Liang; Chengyan Liu; Ran Zeng; Yanan Hou; Hao-Yi Cheng; Aijie Wang (Resources, Conservation and Recycling, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Enhanced bifunctional adsorption of anionic and cationic pollutants by MgAl LDH nanosheets modified montmorillonite via acid-salt activation - Xingjian Dai; Chuan Jing; Kailin Li; Xiaotian Zhang; Dan Song; Li Feng; Xiaoying Liu; Hui Ding; Haodi Ran; Kangwen Zhu; Nan Dai; Shuang Yi; et al. (Applied Clay Science, 2023)

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

Inconsistent patterns of Holocene rainfall changes at the East Asian monsoon margin compared to the core monsoon region - Xin Zhou; Tao Zhan; Ning Tan; Luyao Tu; John P. Smol; Shiwei Jiang; Fangming Zeng; Xiaoyan Liu; Xiangzhong Li; Guangxin Liu; Yi Liu; Ran Zhang; et al. (Quaternary Science Reviews, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Sesquiterpenoids and monoterpenoids from the water decoction of Valeriana officinalis L - Shi-Wei Li; Bian-Xia Xue; Tian-Tian Yang; Ran Li; Mingjie Zhang; Miao Wang; Li-Hua Zhang; Peng Zhang; Yi Zhang; Tao Wang; Shao-Xia Wang; Hong-Hua Wu (Phytochemistry, 2023)

Strengthening ion uptake and mitigating volume change via bimetallic telluride heterojunction for ultrastable K-ion hybrid capacitors - Zhihan Zeng; Wenqi Zhang; Hao Ma; Yuyang Yi; Xueyu Lian; Xianzhong Yang; Ran Cai; Wen Zhao; Jingyu Sun (Chemical Engineering Journal, 2023)

The pre-addition of “blocking” proteins decreases subsequent cellulase adsorption to lignin and enhances cellulose hydrolysis - Jingyun Liu; Jie Wu; Yi Lu; Huaiyu Zhang; Qi Hua; Ran Bi; Orlando Rojas; Scott Renneckar; Senqing Fan; Zeyi Xiao; Jack Saddler (Bioresource Technology, 2023)

Chitin oligosaccharides for the food industry: production and applications - Ran Zhang; Qiong Zhao; Zhenwei Yi; Kaihang Zhang; Jinqi Shi; Liangliang Zhu; Yijia Chen; Jiayang Jin; Liming Zhao (Systems Microbiology and Biomanufacturing, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Intercropping affects the physiology and cadmium absorption of pakchoi, lettuce, and radish seedlings - Le Liang; Xiaomei Li; Huanxiu Li; Xuemei Peng; Ran Zhang; Wanjia Tang; Yiping Dong; Yi Tang (Environmental Science and Pollution Research, 2023)

The roles of ETS transcription factors in liver fibrosis - Li-Ye Zhang; Yong Tan; Xiao-Jie Luo; Jiang-Feng Wu; Yi-Ran Ni (Human Cell, 2022)

Therapeutic effect of the sulforaphane derivative JY4 on ulcerative colitis through the NF-κB-p65 pathway - Xiu-Juan Zhao; Yi-Ran Zhang; Wen-Fei Bai; Tong-Yan Sun; Yu-Fen Yang; Tong-Xin Wang; Cui-Gai Bai (Inflammopharmacology, 2022)

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

Height Variation in the Summer Quasi-Zero Wind Layer over Dunhuang, Northwest China: A Diagnostic Study - Yi Yuan; Yi Liu; Lingkun Ran; Hua Zhang (Journal of Meteorological Research, 2022)

Categorizing objects from MEG signals using EEGNet - Ran Shi; Yanyu Zhao; Zhiyuan Cao; Chunyu Liu; Yi Kang; Jiacai Zhang (Cognitive Neurodynamics, 2022)

Comparison of seismic stability for slopes with tensile strength cut-off and cracks - Ying-bin Zhang; Yan Liu; Ran Yuan; Yi He (Journal of Mountain Science, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Elabela prevents angiotensin II-induced apoptosis and inflammation in rat aortic adventitial fibroblasts via the activation of FGF21–ACE2 signaling - Juan-Juan Song; Mei Yang; Ying Liu; Jia-Wei Song; Xiao-Yan Liu; Ran Miao; Zhen-Zhou Zhang; Yu Liu; Yi-Fan Fan; Qian Zhang; Ying Dong; Xin-Chun Yang; et al. (Journal of Molecular Histology, 2021)

Functional connectivity patterns of the subgenual anterior cingulate cortex in first-episode refractory major depressive disorder - Bochao Cheng; Yajing Meng; Yan Zuo; Yi Guo; Xiuli Wang; Song Wang; Ran Zhang; Wei Deng; Yingkun Guo; Gang Ning (Brain Imaging and Behavior, 2021)

Apportioning above- and below-ground effects of moss biocrusts on soil detachment by overland flow in a subtropical climate - Guan-hua Zhang; Liang Yi; Wen-feng Ding; Xu Lei; Yi-ran Wang; Bao-yang Sun; Jian-ming Li (Journal of Mountain Science, 2021)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

The effect of consecutive ambient air pollution on the hospital admission from chronic obstructive pulmonary disease in the Chengdu region, China - Yi Zhang; Ziyue Wang; Yu Cao; Lifu Zhang; Guan Wang; Fangjie Dong; Ren Deng; Baogen Guo; Li Zeng; Peng Wang; Ruimei Dai; Yu Ran; et al. (Air Quality, Atmosphere & Health, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Effects of Co-Applications of Biochar and Solid Digestate on Enzyme Activities and Heavy Metals Bioavailability in Cd-Polluted Greenhouse Soil - Shuaixing Xue; Fengfen Chen; Yuying Wang; Zhijiang Shao; Congguang Zhang; Ling Qiu; Yi Ran; Li He (Water, Air, & Soil Pollution, 2021)

Concatenated data and dense taxon sampling clarify phylogeny and ecological transitions within Hypotricha - Jiahui Xu; Mark Wilkinson; Miaoying Chen; Qi Zhang; Ran Yang; Zhenzhen Yi (Zoologica Scripta, 2021)
Ciliates are single‐cell eukaryotes playing important roles in various ecosystems. Phylogenetic relationships within Hypotricha, one of the most polymorphic and highly derived ciliate groups, remain uncertain. Previous studies suggested that low genetic divergence might be the reason for poorly supported SSU rDNA tree topologies, despite the high morphological diversity of this group. In this study, we substantially increase the number of available hypotrich LSU rDNA gene sequences by the addition of 857 environmental sequences, and we investigate whether a more divergent gene and dense taxon sampling could better resolve the phylogeny of Hypotricha and shed light on the patterns of ecological transitions in the evolutionary history of the group. Pairwise distances of LSU rDNA sequences are generally higher than those for SSU rDNA within each order of Hypotricha, and both concatenated rDNA and LSU rDNA trees provide more resolution for hypotrich phylogenetics. Three traditional (morphology based) hypotrich orders, Stichotrichida, Sporadotrichida and Urostylida, are polyphyletic, but a monophyletic core Urostylida are found in our trees. A brackish/marine environment is inferred as ancestral within Hypotricha, with subsequent ecological diversification into freshwater, soil environments before the origin of major clades and some transitions back to the marine. However, inferred ecological transitions in Hypotricha are influenced by genes, methods and taxa.

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Association of Corticotropin-Releasing Hormone Receptor-1 Gene Polymorphisms and Personality Traits with Violent Aggression in Male Adolescents - Li Liu; Yi Qiao; Yang Shao; Shun-ying Yu; Chen Zhang; Ran Zhang; Dong-xiang Wang; Min Zhao; Bin Xie (Journal of Molecular Neuroscience, 2020)

De Novo and Inherited SETD1A Variants in Early-onset Epilepsy - Xiuya Yu; Lin Yang; Jin Li; Wanxing Li; Dongzhi Li; Ran Wang; Kai Wu; Wenhao Chen; Yi Zhang; Zilong Qiu; Wenhao Zhou (Neuroscience Bulletin, 2019)

Automated Detection of Vulnerable Plaque for Intravascular Optical Coherence Tomography Images - Ran Liu; Yanzhen Zhang; Yangting Zheng; Yaqiong Liu; Yang Zhao; Lin Yi (Cardiovascular Engineering and Technology, 2019)

Analysis and Simulation of the Stratospheric Quasi-zero Wind Layer over Korla, Xinjiang Province, China - Rui Yang; Lingkun Ran; Yuli Zhang; Yi Liu (Advances in Atmospheric Sciences, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Trends of sea surface temperature and sea surface temperature fronts in the South China Sea during 2003–2017 - Yi Yu; Hao-Ran Zhang; Jiangbo Jin; Yuntao Wang (Acta Oceanologica Sinica, 2019)

Identification and detection sensitivity of Microcystis aeruginosa from mixed and field samples using MALDI-TOF MS - Li-Wei Sun; Wen-Jing Jiang; Jun-Yi Zhang; Wen-Qian Wang; Yang Du; Hiroaki Sato; Masanobu Kawachi; Ran Yu (Environmental Monitoring and Assessment, 2018)

Genetic mapping and salt tolerance of a novel D1-allelic mutant of rice (Oryza sativa L.) - Wei-jiang Tian; Xiao-qiong Zhang; Xiao-wen Wang; Jia Xie; Yang-yang Li; Ying Sun; Yi-ran Tao; Yu-zhen Xiong; Xian-chun Sang (Acta Physiologiae Plantarum, 2018)

The mitochondrial genome of red-necked phalarope Phalaropus lobatus (Charadriiformes: Scolopacidae) and phylogeny analysis among Scolopacidae - Wei Liu; Chaochao Hu; Wenli Xie; Peng Chen; Yi Zhang; Ran Yao; Kexin Li; Qing Chang (Genes & Genomics, 2018)

Novel Magnetic Nanocarbon and Its Adsorption of Hg and Pb from Water - Kai Guo; Steven L. Larson; John H. Ballard; Zikri Arslan; Rong Zhang; Yong Ran; Yi Su; Fengxiang X. Han (Water, Air, & Soil Pollution, 2018)

Long-term agronomic practices alter the composition of asymbiotic diazotrophic bacterial community and their nitrogen fixation genes in an acidic red soil - Weibing Xun; Wei Li; Ting Huang; Yi Ren; Wu Xiong; Youzhi Miao; Wei Ran; Dongchu Li; Qirong Shen; Ruifu Zhang (Biology and Fertility of Soils, 2018)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

The Effect of Selenium on the Cd-Induced Apoptosis via NO-Mediated Mitochondrial Apoptosis Pathway in Chicken Liver - Runxiang Zhang; Ran Yi; Yanju Bi; Lu Xing; Jun Bao; Jianhong Li (Biological Trace Element Research, 2017)

Comparative proteomic analysis of apple branches susceptible and resistant to ring rot disease - Zhang Cai-xia; Tian Yi; Zhang Li-yi; Zong Ze-ran; Cong Pei-hua (European Journal of Plant Pathology, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Isolation, Characterization, and Bioinformatic Analyses of Lytic Salmonella Enteritidis Phages and Tests of Their Antibacterial Activity in Food - Han Han; Xiaoting Wei; Yi Wei; Xiufeng Zhang; Xuemin Li; Jinzhong Jiang; Ran Wang (Current Microbiology, 2017)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Enhanced hydroxyl radical generation in the combined ozonation and electrolysis process using carbon nanotubes containing gas diffusion cathode - Donghai Wu; Guanghua Lu; Ran Zhang; Qiuhong Lin; Zhenhua Yan; Jianchao Liu; Yi Li (Environmental Science and Pollution Research, 2015)

Development of a dot blot macroarray and its use in gene expression marker-assisted selection for iron deficiency tolerant apple rootstocks - Mingtao Zhu; Ran Wang; Penghao Kong; Xinzhong Zhang; Yi Wang; Ting Wu; Wensuo Jia; Zhenhai Han (Euphytica, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process - Jian-Jun Yang; Meng-Xi Huang; Qian-Yi Wu; Hao-Ran Zhang (Contributions to Mineralogy and Petrology, 2014)

Krüppel-like Factor 8 Ameliorates Alzheimer's Disease by Activating β-Catenin - Ran Yi; Benwei Chen; Jing Zhao; Xiaorong Zhan; Liming Zhang; Xiaomin Liu; Qi Dong (Journal of Molecular Neuroscience, 2014)

Enhanced viability of Lactobacillus reuteri for probiotics production in mixed solid-state fermentation in the presence of Bacillus subtilis - Yi-Ran Zhang; Hai-Rong Xiong; Xiao-Hua Guo (Folia Microbiologica, 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Active surveillance of renal masses in von Hippel-Lindau disease: growth rates and clinical outcome over a median follow-up period of 56 months - Jin Zhang; Jia-Hua Pan; Bai-Jun Dong; Wei Xue; Dong-ming Liu; Yi-Ran Huang (Familial Cancer, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

An easy-to-use site-directed mutagenesis method with a designed restriction site for convenient and reliable mutant screening - Bao-zhong Zhang; Xin Zhang; Xiao-ping An; Duo-liang Ran; Yu-sen Zhou; Jun Lu; Yi-gang Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Role of DNA in Bacterial Aggregation - Hui-Hui Liu; Yi-Ran Yang; Xin-Cheng Shen; Zhi-Ling Zhang; Ping Shen; Zhi-Xiong Xie (Current Microbiology, 2008)

Microcalorimetric Study on the Effect of Ce3+ on Halobacterium halobium R1 - Yi Liu; Jun Yin; Ran Li; Li Li; Jie Dai; Ye-Zhong Zhang; Ping Shen (Biological Trace Element Research, 2008)